Peak Power Output Is Similarly Recovered After Three- and Five-Days' Rest Following Sprint Interval Training in Young and Older Adults - Zerbu Yasar; Susan Dewhurst; Lawrence D. Hayes (MDPI AG, 2019)
(1) Background: High-intensity interval training (HIIT) exerts effects indicative of improved health in young and older populations. However, prescribing analogous training programmes is inappropriate, as recovery from HIIT is different between young and older individuals. Sprint interval training (SIT) is a derivative of HIIT but with shorter, maximal effort intervals. Prior to prescribing this mode of training, it is imperative to understand the recovery period to prevent residual fatigue affecting subsequent adaptations. (2) Methods: Nine older (6M/3F; mean age of 70 ± 8 years) and nine young (6M/3F; mean age of 24 ± 3 years) participants performed a baseline peak power output (PPO) test. Subsequently, two SIT sessions consisting of three repetitions of 20 s ‘all-out’ stationary cycling bouts interspersed by 3 minutes of self-paced recovery were performed. SIT sessions were followed by 3 days’ rest and 5 days’ rest on two separate occasions, in a randomised crossover design. PPO was measured again to determine whether recovery had been achieved after 3 days or after 5 days. (3) Results: Two-way repeated measure (age (older, young) × 3 time (baseline, 3 days, 5 days)) ANOVA revealed a large effect of age (p = 0.002, n2p = 0.460), with older participants having a lower PPO compared to young participants. A small effect of time (p = 0.702, n2p = 0.022), and a medium interaction between age and time (p = 0.098, n2p = 0.135) was observed. (4) Conclusions: This study demonstrates both young and older adults recover PPO following 3 and 5 days’ rest. As such, both groups could undertake SIT following three days of rest, without a reduction in PPO.